Virus-like particles of nodavirus displaying the receptor binding domain of SARS-CoV-2 spike protein: a potential VLP-based COVID-19 vaccine - Kumar, Kiven; Tan, Wen Siang; Arshad, Siti Suri; Ho, Kok Lian (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Since the outbreak of the coronavirus disease 2019 (COVID-19), various vaccines have been developed for emergency use. The efficacy of the initial vaccines based on the ancestral strain of severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) has become a point of contention due to the emergence of new variants of concern (VOCs). Therefore, continuous innovation of new vaccines is required to target upcoming VOCs. The receptor binding domain (RBD) of the virus spike (S) glycoprotein has been extensively used in vaccine development due to its role in host cell attachment and penetration. In this study, the RBDs of the Beta (β) and Delta (δ) variants were fused to the truncated Macrobrachium rosenbergii nodavirus capsid protein without the protruding domain (CΔ116-MrNV-CP). Immunization of BALB/c mice with the virus-like particles (VLPs) self-assembled from the recombinant CP showed that, with AddaVax as an adjuvant, a significantly high level of humoral response was elicited. Specifically, mice injected with equimolar of adjuvanted CΔ116-MrNV-CP fused with the RBD of the β- and δ-variants increased T helper (Th) cell production with a CD8+/CD4+ ratio of 0.42. This formulation also induced proliferation of macrophages and lymphocytes. Overall, this study demonstrated that the nodavirus truncated CP fused with the SARS-CoV-2 RBD has potential to be developed as a VLP-based COVID-19 vaccine.